Can CD34+CD38− lymphoblasts, as likely leukemia stem cells, be a prognostic factor in B-cell precursor acute lymphoblastic leukemia in children? - Stolpa, Weronika; Mizia-Malarz, Agnieszka; Zapała, Magdalena; Zwiernik, Bartosz (Frontiers in Pediatrics, 2023)
Background CD34+CD38− lymphoblasts as likely leukemia stem cells (LSCs) may be responsible for a worse response to treatment and may be a risk factor for recurrence in B-cell precursor acute lymphoblastic leukemia (BCP-ALL). Objective The study objective was to assess the prognostic role of CD34+CD38− lymphoblasts in bone marrow on the day of BCP-ALL diagnosis. Methods 115 patients with BCP-ALL, the median age of 4.5 years (range 1.5–17.9 years), gender: female 63 (54.8%) with BCP-ALL were enrolled; Group I (n = 90)—patients with CD34+CD38+ antigens and Group II (n = 20)—patients with CD34+CD38− antigens on the lymphoblast surface. Results A worse response on Days 8, 15, and 33 of therapy and at the end of treatment in Group II (CD34+CD38−) was more often observed but these differences were not statistically significant. A significantly higher incidence of BCP-ALL recurrence was in Group II. Conclusions 1. In BCP-ALL in children, the presence of CD34+CD38− lymphoblasts at the diagnosis does not affect the first remission. 2. In BCP-ALL in children, the presence of CD34+CD38− lymphoblasts at the diagnosis may be considered an unfavorable prognostic factor for disease recurrence. 3. It is necessary to further search for prognostic factors in BCP-ALL in children.